Neurofibromatosis irides with flat vertebra-A case report - Saxena Sandeep; Saxena R (Indian Journal of Ophthalmology, 1991)
Bilateral multiple iris nodules with thickened corneal nerves and flat fifth thoracic vertebra is being reported.